Unprotected anal Intercourse among Iranian Intra-Venous Drug Users - Mirabi, Parvaneh; Yarmohammadi Vasel, Mosayeb; Moazen, Babak; Sehat, Mahmoud; Rezazadeh, Majid; Ahmadi, Khodabakhsh (Frontiers in Public Health, 2013)
Purpose: To assess the prevalence and associated factors of unprotected anal intercourse among Iranian male heterosexual Intra-Venous Drug Users (IDUs). Methods: In a cross sectional study 360 male heterosexual IDUs were sampled from streets of eight different geographical parts of Iran. Variables such as socio-demographics, HIV knowledge (10 items) and HIV attitude (16 items) were entered to a logistic regression to determine the predictors of unprotected anal intercourse during the past month. Results: From all, 20.8% reported unprotected anal intercourse during the past month. HIV knowledge was not significantly different among IDUs with and without unprotected anal intercourse. High age (OR=0.954, 95% CI=0.916-0.992) was associated with a lower likelihood of unprotected anal intercourse, while being not married (OR=2.301, 95% CI=1.151-4.601), and high perceived HIV risk (OR=1.776, 95% CI=1.376-2.290) were associated with a higher likelihood of unprotected anal intercourse. Conclusions: Although the results might not be generalizable to all Iranian IDUs, this study findings may still be helpful for design and implementation of public health programs in Iran to prevent sexual transmission of HIV through IDUs.